LABOR PRODUCTIVITY AS A FACTOR OF - M. Uruymagov (Вестник Северо-Кавказского федерального университета)
The article discusses the issues of labor productivity as a keyfactor in increasing the competitiveness of the national economy. The analysis of labor productivity indicators is carried out, a number of methodological and organizational problems that hinder the growth of labor productivity are highlighted. The national project ((Increasing labor productivity and supporting employment)} is intended to unite the efforts of federal and regional authorities, and businesses to ensure the growth of labor productivity, to ensure the replication of the best regional practices and experience of advanced enterprises in this regard. A prerequisite for the successful implementation of the national project is the development and implementation ofregional programs to increase labor productivity, as well as relevant programs at the enterprise level. The article focuses on the problem of increasing labor productivity in the Republic of North Ossetia-Alania. The practical recommendations outlined in the article are based on the successful experience of the Vladikavkaz technological center «Baspik».